2023
DOI: 10.31662/jmaj.2023-0005
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Vertebral Compression Fracture in a Patient with Idiopathic Normal Pressure Hydrocephalus

Abstract: Idiopathic normal pressure hydrocephalus (iNPH) with gait disturbance can be effectively treated with a cerebrospinal fluid shunt. Furthermore, balloon kyphoplasty (BKP) is a successful minimally invasive treatment for osteoporotic vertebral compression fractures (VCFs). This case report presents the surgical management of an elderly patient with iNPH who presented after a VCF due to a fall. A 77-year-old woman who had been experiencing progressive gait disturbance for five years reported experiencing back pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…[ 4 ] VCFs are a global burden that temporarily or permanently affects millions of elderly people, and balloon kyphoplasty (BKP) is a widely accepted minimally invasive surgical technique for the treatment of osteoporotic VCFs. [ 5 ] Although a case report on the presence of iNPH in patients with VCFs has been published [ 15 ] to the best of our knowledge, no previous study has reported the prevalence of iNPH in elderly patients before the diagnosis of VCFs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] VCFs are a global burden that temporarily or permanently affects millions of elderly people, and balloon kyphoplasty (BKP) is a widely accepted minimally invasive surgical technique for the treatment of osteoporotic VCFs. [ 5 ] Although a case report on the presence of iNPH in patients with VCFs has been published [ 15 ] to the best of our knowledge, no previous study has reported the prevalence of iNPH in elderly patients before the diagnosis of VCFs.…”
Section: Introductionmentioning
confidence: 99%